2015
DOI: 10.1371/journal.pone.0118659
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Expression of Pontin in Renal Cell Carcinoma Correlates with Tumor Invasion, Metastasis and Patients’ Survival

Abstract: Renal cell carcinoma (RCC) is the most lethal of all genitourinary malignancies. Distant metastasis represents the major cause of death in patients with RCC. Recent studies have implicated the AAA+ ATPase pontin in many cellular activities that are highly relevant to carcinogenesis. In this study, we demonstrate for the first time that pontin was up-regulated in RCC, and plays a previously unknown pro-invasive role in the metastatic progression of RCC through epithelial-to-mesenchymal transition (EMT) pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
7
25
1
Order By: Relevance
“…During RCC tumor genesis and progression, dedifferentiation accompanied by epithelial mesenchymal transition (EMT) takes place (26,27). During transition the tumor cells lose epithelial (E)-cadherin and gain neural (N)-cadherin (26,28). In all three RCC cell lines used in this study, application of amygdalin for 24 h caused a significant decrease in N-cadherin expression, which indicates re-differentiation.…”
Section: Discussionmentioning
confidence: 82%
“…During RCC tumor genesis and progression, dedifferentiation accompanied by epithelial mesenchymal transition (EMT) takes place (26,27). During transition the tumor cells lose epithelial (E)-cadherin and gain neural (N)-cadherin (26,28). In all three RCC cell lines used in this study, application of amygdalin for 24 h caused a significant decrease in N-cadherin expression, which indicates re-differentiation.…”
Section: Discussionmentioning
confidence: 82%
“…In the excretory system (Table 1 ), overexpression of the two ATPases was found in renal cell carcinoma (RCC) (Ren et al, 2013 ; Zhang et al, 2015 ). Like in HCC patients, cytoplasmic localization of Pontin and Reptin in RCC was found to be correlated with metastasis and unfavorable outcome (Rousseau et al, 2007 ; Haurie et al, 2009 ; Ren et al, 2013 ; Zhang et al, 2015 ). Whether correlation with localization of the protein can apply to other cancer types where cytoplasmic expression was also shown remains to be investigated.…”
Section: Roles Of Pontin/reptin In Cancermentioning
confidence: 99%
“…Studies in a variety of cancer cell lines have consistently demonstrated that downregulation of either Pontin or Reptin may lead to cell cycle arrest at the G1/S phase checkpoint, resulting in the accumulation of cells in G1 and a reduction of cells in all other phases of the cell cycle (S, G2/M) (Rousseau et al, 2007 ; Haurie et al, 2009 ; Menard et al, 2010 ; Osaki et al, 2013 ; Ren et al, 2013 ; Breig et al, 2014 ; Zhang et al, 2015 ; Yuan et al, 2016 ). G1/S transition is regulated by many proteins and pathways that are normally inactivated until entry into S phase is signaled (Otto and Sicinski, 2017 ).…”
Section: Role Of Pontin/reptin In Specific Cellular Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Interacts with oncogene c-MYC and β-catenin. Roles in cell growth and viability [231][232][233][234][235][236][237][238]. In a mouse model of liver cancer, accumulation of E2f1 recruits the RUVBL1/RUVBL2 complex that opens the chromatin conformation at E2f target genes and amplifies the E2f transcriptional response during cancer progression.…”
Section: Actr5 (Ino80m) *mentioning
confidence: 99%